RNA Binding Proteins in Eye Development and Disease: Implication of Conserved RNA Granule Components - Dash, Soma (Wiley Interdiscip Rev RNA, 2016)
The molecular biology of metazoan eye development is an area of intense investigation. These efforts have led to the surprising recognition that although insect and vertebrate eyes have dramatically different structures, the orthologs or family members of several conserved transcription and signaling regulators such as Pax6, Six3, Prox1 and Bmp4 are commonly required for their development. In contrast, our understanding of post-transcriptional regulation in eye development and disease, particularly regarding the function of RNA binding proteins (RBPs), is limited. We examine the present knowledge of RBPs in eye development in the insect model Drosophila, as well as several vertebrate models such as fish, frog, chicken and mouse. Interestingly, of the 42 RBPs that have been investigated with for their expression or function in vertebrate eye development, 24 (~60%) are recognized in eukaryotic cells as components of RNA granules such as Processing bodies (P-bodies), Stress granules, or other specialized ribonucleoprotein (RNP) complexes. We discuss the distinct developmental and cellular events that may necessitate potential RBP/RNA granule-associated RNA regulon models to facilitate post-transcriptional control of gene expression in eye morphogenesis. In support of these hypotheses, three RBPs and RNP/RNA granule components Tdrd7, Caprin2 and Stau2 are linked to ocular developmental defects such as congenital cataract, Peters anomaly and microphthalmia in human patients or animal models. We conclude by discussing the utility of interdisciplinary approaches such as the bioinformatics tool iSyTE (integrated Systems Tool for Eye gene discovery) to prioritize RBPs for deriving post-transcriptional regulatory networks in eye development and disease.